Pengaruh Terapi Rendam Kaki Air Hangat Terhadap Tekanan Darah Pada Penderita Hipertensi di Puskesmas Bailang Kota Manado - Sali M. Papeti; Zainar Kasim; Ismawati Ismawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension is a condition where systolic blood pressure is more than 120 mmHg and diastolic pressure is more than 80 mmHg which can be measured in millimeters of mercury (mmHg). In addition to pharmacological therapy, hypertension management can also use non-pharmacological therapies, one of which is foot soak therapy in warm water. The purpose of this research is to determine effect of warm water foot soak therapy on blood pressure in patients with hypertension at Bailang Health Center Manado City. This study uses a pre-experimental method with a one-group pretest-posttest design without a comparison group. The population with the result that 165 people patients diagnosed with hypertension. The sampling process used a probability sampling technique with the result that 15 respondents. Data collection was observations. The data were analyzed using the Wilcoxon test with a significance value (?) of 0.05. From the results of the study was that there was an effect of warm water foot soak therapy on blood pressurein patients with hypertension at Bailang Health Center Manado City with a value of p = 0.008. This p value is smaller than the value of a = 0.05. The conclusion of this study was that there was an effect of warm water foot soak therapy on blood pressurein patients with hypertension. This p value is smaller than the value of a = 0.05. It is hoped that the respondents will be able to take advantage of warm water foot soak therapy as an alternative in lowering blood pressure and this can also be done regularly.